Digital teaching tools: An ELT methods e-module to foster critical thinking skills for English student teachers in Indonesia - Susanti, Arik; Rachmajanti, Sri; Suryati, Nunung; Astuti, Utari (International Journal of Innovative Research and Scientific Studies, 2025)
The study aims to investigate whether the ELT Methods e-module could improve student teachers’ critical thinking (CT) skills. The research design was an experimental study conducted at a public university in Surabaya, Indonesia, that provides a specialized program in English Education. A total of 124 samples were evenly divided into two groups: the experimental and control groups, which consisted of 62 students. The instruments were pre and post-tests in essay format. Inferential statistics were employed to analyze the data. The findings indicate that the experimental group has an average score of 84.97, whereas the control group averages 76.48. This indicates that the ELT Methods e-module has the potential to enhance student teachers’ critical thinking skills. Various strategies are employed to foster their CT skills, such as one-minute papers, discussions, online collaboration, case study analysis, and real project activities. Thus, integrating digital learning tools can enhance the development of CT skills among future English teachers. It implies the need for innovative instructional designs that combine technology with active learning strategies to better prepare student teachers for 21st-century classroom challenges.